Reactivity of Soluble Fibrin Assays with Plasmic Degradation Products of Fibrin and in Patients Receiving Fibrinolytic Therapy - McCarron, Bonnie I.; Marder, Victor J.; Francis, Charles W. (Thrombosis and Haemostasis, 1999)
The ability to identify the products of thrombin and plasmin action on fibrinogen is important in patients with thrombotic and fibrinolytic disorders. New assays have been developed for “soluble fibrin” which represents soluble derivatives other than fibrinopeptides formed from fibrinogen by thrombin. These assays are either immunological, using antibodies for fibrin-specific neoepitopes, or functional and based on the cofactor activity of soluble fibrin in the tissue plasminogen activator (t-PA)-mediated conversion of plasminogen to plasmin. As plasmic derivations of fibrin share structural features with soluble fibrin, they may be reactive with assays for soluble fibrin. Therefore, we prepared plasmic digests of fibrin and determined the degree of reactivity with four soluble fibrin assays. Three assays used Mabs directed toward the fibrin-specific neoepitopes at α17-23 (A), γ312-324 (B) and α17-78 (D). A fourth (C) was based on t-PA co-factor activity. Tests A and C demonstrated marked crossreactivity with fibrin degradation products, and digests containing the largest derivatives showed greatest reactivity. Plasmic derivatives of crosslinked fibrin had greater reactivity than those of non-crosslinked fibrin. Tests B and D demonstrated minimal reactivity with plasmic derivatives of crosslinked or of non-crosslinked fibrin. Samples from patients with lower limb peripheral arterial occlusion were assayed for soluble fibrin, D-dimer and fibrinogen at presentation and eight hours after thrombolytic therapy. Variable results were seen at presentation with elevations in 13, 1, 0 and 4 of 19 patients using Tests A, B, C and D, respectively. After fibrinolytic therapy, marked increases in soluble fibrin levels were observed up to 600-fold above normal. A strong correlation between baseline levels was observed with Test B and Test D, which showed the least cross-reactivity with plasmic derivations. After thrombolytic therapy there were either weak or no correlations among the different assays. The results demonstrate that assays for soluble fibrin may react with plasmic derivatives of fibrin and this must be considered in interpreting clinical results.
Keywords: Soluble fibrin; fibrin(ogen) degradation products; fibrinolysis; peripheral vascular disease; fibrinolytic therapy; D-dimer